2013
DOI: 10.1002/jmri.24224
|View full text |Cite
|
Sign up to set email alerts
|

Registration of dynamic contrast‐enhanced MRI of the common carotid artery using a fixed‐frame template‐based squared‐difference method

Abstract: Purpose This study examines template-based squared-difference registration for motion correction in dynamic contrast-enhanced (DCE) MRI studies of the carotid artery wall and compares the results of fixed-frame template-based registration with a previously proposed consecutive-frame registration method. Materials and Methods Ten T1-weighted black-blood, turbo spin-echo DCE-MRI studies of the carotid artery wall were used to test template-based squared-difference registration. An intermediate image from each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…DCE images were coregistered by using a rigid body registration algorithm which searches for the optimal rotation and translational parameters by minimizing the mean squared difference between the moving and the reference image as cost function [38].…”
Section: Quantitative Analysismentioning
confidence: 99%
“…DCE images were coregistered by using a rigid body registration algorithm which searches for the optimal rotation and translational parameters by minimizing the mean squared difference between the moving and the reference image as cost function [38].…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Especially in the voxelwise analysis, movement of the subject during acquisition of the different DCE-MRI sequence time frames may pose a problem. A solution is to manually shift individual time frames to correctly align the images, or alternatively, to use post-processing methods for automated movement correction and noise reduction [ 20 , 22 ].…”
Section: Dce-mri Methods To Study Plaque Microvasculaturementioning
confidence: 99%
“…Overview of studies investigating the atherosclerotic plaque microvasculature using dynamic contrast-enhanced MRI: subjects (human or rabbits), analysis method (quantitative or semi-quantitative), main study purpose, and study outcome are shown Reference Subjects Main study purpose Main study outcome Chen et al [ 18 ] Patients with CVD (AIM-HIGH Trial [ 19 ] Scan-rescan reproducibility Moderate reproducibility for K trans (Patlak) with a 25 % coefficient of variation. To limit dropout, intensive operator training, optimized imaging, and quality control is required Kerwin et al [ 20 ] CEA patients Method development Development of a motion correcting and noise reducing algorithm for the analysis of DCE-MRI of carotid arteries Kerwin et al [ 21 ] Patients with a carotid lesion ≥ AHA type IV Method comparison Quantitative enhancement characteristics, such as K trans (Patlak), depend on the used contrast medium (gadobenate dimeglumine vs gadodiamide) Ramachandran et al [ 22 ] Humans with CVD risk Method development Development of a registration method for alignment of different time frames of DCE-MRI of carotid arteries Chen et al [ 23 ] Humans with advanced carotid disease Method development Extended graphical model exhibits a reduced bias in K trans estimation compared to the Patlak model Van Hoof et al [ 24 ] Symptomatic patients (30–99 % carotid stenosis) Method comparison Comparison between phase- and magnitude-based vascular input functions and resulting effect on pharmacokinetic parameters. No signal saturation due to blood flow for phase-based determined vascular input function Calcagno et al [ 25 ] Humans with CVD risk Method development Demonstration of feasibility of simultaneous VIF and vessel wall imaging (extended Tofts) Wan et al [ 26 ] NZW Rabbit a,b Method development Spatio-temporal texture based features (like AUC) are able to distinguish between vulnerable and stable plaques.…”
Section: Introductionmentioning
confidence: 99%
“…Several registration methods are available for registration of MR images, such as nonrigid-body registration for the kidneys 15 , deformable and rigid-body registration for prostate cancer 16 , rigid-body registration for gliomas 17 , and fixed-frame template-based squareddifference registration for abdominal DCE-MRI data on the liver 18 . The two most commonly used registration methods with medical images are deformable registration and rigid-body registration.…”
Section: Introductionmentioning
confidence: 99%